Melissa officinalis extract improved high-fat-diet-induced anxiety-like behaviors, depression, and memory impairment by regulation of serum BDNF levels in rats - Kazem Hatami; Majid Hassanpourezatti; Mohsen Khalili (Avicenna Journal of Phytomedicine)
Objective: Melissa officinalis (MO) hydroalcoholic extract has shown neuroprotective effects. We assess the possible therapeutic effects of Melissa officinalis extract (MOE) on blood biochemical and Brain-Derived Neurotrophic Factor (BDNF) levels as well as neurobehavioral consequences of high-fat-diet (HFD)-induced obese rats.Materials and Methods: Eighty male Wistar rats weighing between 180 and 220 g were divided into two groups at the beginning of the experiment and fed with normal diet (ND) or HFD for 5 weeks. Then, each group was divided into four subgroups (10 rats in each group) and treated daily with MOE (50, 100, 150 mg/kg, intraperitoneal) or vehicle for another two weeks. At the end of the experiments, fasting blood glucose (FBG), blood lipid profile, and serum brain-derived neurotrophic factor (BDNF) levels were measured. The sucrose preference test (anhedonia and depression), open field test (locomotor), elevated plus maze (anxiety), Y-maze (working memory), and Morris water maze test (spatial memory) were done.Results: Feeding with HFD for 7 weeks caused obesity, anhedonia, anxiety, depression and learning and memory disorders in rats and a decrease in serum BDNF level. Administration of MOE at 100 or 150 mg/kg to HFD-fed rats decreased weight gain, FBG, and serum levels of total low-density lipoprotein cholesterol and increased serum BDNF levels. It also improved changes in locomotor activity, anxiety, depression, and learning and memory in HFD-fed rats.Conclusion: The results show that MOE has a therapeutic effect on model rats with HFD-induced metabolic and neurobehavioral abnormalities through regulation of BDNF secretion.